AN EXPLORATORY STUDY OF THE SOCIAL MEDIA MARKETING ROLE IN MEASURING BUSINESS PERFORMANCE AMONG STUDENT ENTREPRENEURS - Kelvin Yong; Nur Thara Atikah Zainal (International Journal of Accounting, Finance and Business, 2021)
The purpose of this research is to examine the social media marketing roles inmeasuring business performance among student entrepreneurs. Secondly, to analyse whichsocial media platform is often used by students to sell and promote their business. Due to apandemic outbreak, students are unable to sell face-to-face in the university due to themovement control order (MCO). As a result, students are required to sell online via socialmedia platforms. Therefore, a study needs to be established to analyse the effectiveness ofdigital entrepreneurship in the University syllabus. Especially in social media marketing topics,Convenience sampling was used to distribute the survey questionnaire to APK students inUniversiti Malaysia Sabah. The findings of this study indicated that social media marketing hasa positive relationship with business performance. Most of the respondents used Facebook,Instagram, WhatsApp, and e-business portfolio blogs to promote and sell their business. Thisstudy will help lecturers develop a comprehensive and integrated entrepreneurship module.The results of the study can produce improvements in teaching and learning, especially in socialmedia marketing usage how students promote and sell online.